2018
DOI: 10.1038/s41598-018-31941-1
|View full text |Cite
|
Sign up to set email alerts
|

Tuning electronic properties of transition-metal dichalcogenides via defect charge

Abstract: Defect engineering is a promising route for controlling the electronic properties of monolayer transition-metal dichalcogenide (TMD) materials. Here, we demonstrate that the electronic structure of MoS2 depends sensitively on the defect charge, both its sign and magnitude. In particular, we study shallow bound states induced by charged defects using large-scale tight-binding simulations with screened defect potentials and observe qualitative changes in the orbital character of the lowest lying impurity states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…1(f). States A and B have a spherical shape reminiscent of an s-type orbital, whereas state C has three lobes and a node at its center, indicative of a trigonally warped 2p-type orbital [16]. With a lateral dimension of about 1.5 − 2 nm, the localized defect states are closely confined, as compared to the Rydberg states recently reported for ionized defects in bulk black phosphorus which extend more than ten nanometers [28].…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…1(f). States A and B have a spherical shape reminiscent of an s-type orbital, whereas state C has three lobes and a node at its center, indicative of a trigonally warped 2p-type orbital [16]. With a lateral dimension of about 1.5 − 2 nm, the localized defect states are closely confined, as compared to the Rydberg states recently reported for ionized defects in bulk black phosphorus which extend more than ten nanometers [28].…”
Section: Methodsmentioning
confidence: 74%
“…Instead, in 2D semiconductors the dielectric response is relatively weak and highly anisotropic, which gives rise to strongly bound excitons that dominate their optical response [14,15]. Unconventional screening of charged defects in monolayer TMDs with multi-valley band structure and large spinorbit effects can also give rise to bound defect states with unusual properties, e.g., the prediction that the most strongly bound acceptor state switches from being of K/K -valley character to Γ-valley character at a critical value of the defect charge [16].…”
mentioning
confidence: 99%
“…The prosperity of graphene motivated the arising of other 2D materials, such as silicene, phosphorene, arsenene, and antimonene as well as transition metal dichalcogenides (TMDs) . Single‐layer TMDs (MX 2 , M = TM, X = S, Se, Te) have become a hotspot of theoretical and experimental researches because of their promising applications in hydrogen evolution reaction catalysts, nanoelectronics, nanophotonics, absorber layer in solar cells, anode materials, field‐effect transistors, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The prosperity of graphene motivated the arising of other 2D materials, such as silicene, [1] phosphorene, [2] arsenene, and antimonene [3,4] as well as transition metal dichalcogenides (TMDs). [5][6][7][8][9][10] Single-layer TMDs (MX 2 , M ¼ TM, X ¼ S, Se, Te) have become a hotspot of theoretical and experimental researches because of their promising applications in hydrogen evolution reaction catalysts, nanoelectronics, nanophotonics, absorber layer in solar cells, anode materials, field-effect transistors, and so on. For example, Choi et al have reported that TMDs can be used as addition materials for the Li-Se batteries to prevent the decomposition of LiPSe, in addition, the TMDs can capture LiPSe more efficiently than graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The a 1 state exhibits very little dispersion consistent with the out-of-plane d 3z 2 −r 2 orbital character at Γ where the weak dispersion of the host MoS 2 bands is described by a large effective mass. 68 In the language of effective mass theory (EMT), the binding energy of the a 1 state is dominated by the central cell correction. 63 In the rightmost panel of Fig.…”
Section: A Single Impurity Limit: V In Mos2mentioning
confidence: 99%